An electronic language teaching system for visual-disabled - Aris, Ishak; Yeoh, Sing Hsia (2011)
The present invention relates to an electronic language teaching system for visual-disabled. The present invention comprising a computer having a Braillecode-aided keyboard configured to provide input character; a microphone; a software including graphical user interface configured to process the input character; a speaker configured to provide audio output; and a tactile feedback module connected to the computer configured to provide physical and visual output characterized in that the tactile feedback module further comprising: a retractable means configured to form and indicate Braille characters physically and visually. The above provision is advantageous as reduces manpower to teach the visual-diasabled by providing computer-implemented language teaching system.